Peran Pendidikan Kewirausahaan Terhadap Kesiapan Berwirausaha pada Peserta Didik SMKN Sukaresik - Cucu Herlina; Krisna Sujaya; Ismail Yusuf (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Entrepreneurship education plays a major role in increasing the number of entrepreneurs in Indonesia. Because entrepreneurs create jobs for other in addition to themselves, the unemployment rate may decline as their numbers rise. Students must therefore be ready for entrepreneurship. Understanding the entrepreneurial mindset and preparedness of SMKN Sukaresik students is the aim of this study. The study discovered that while unemployment is rising, students are not as prepared for entrepreneurship. This result from the inadequate application of entrepreneurship education in the educational setting. The purpose of the study was to determine how education affected the entrepreneurial readiness of SMKN Sukaresik students. This study combined descriptive and verification methods with quantitative method. The research population consisted of 102 SMKN Sukaresik online business and marketing majors. The Slovin formula was used to generate a sample of 50 responders. The findings demonstrated that entrepreneurship education has a positive impact on SMKN Sukaresik students’ entrepreneurial readiness. A coefficient of determination of 0,555 indicates that entrepreneurship education has a 55,5% impact on entrepreneurial readiness, while 44,5% is attributable to other factors not included in the study.